2007
DOI: 10.1159/000101304
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin and ZO-1: Shuttle Molecules Involved in Tumor Invasion-Associated Epithelial-Mesenchymal Transition Processes

Abstract: The cytoplasmic/nuclear relocalization of β-catenin and ZO-1 from the adherens and tight junctions are common processes of the epithelial-mesenchymal transition (EMT) associated with tumor invasion. Data are now accumulating to demonstrate that these molecules, which shuttle between the plasma membrane and the nucleus or the cytosol, are involved in signaling pathways, and contribute to the regulation of genes such as vimentin or matrix metalloproteinase-14 which are turned on during EMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 67 publications
4
94
1
Order By: Relevance
“…In contrast, the localisation of vimentin in both control and EGF-treated cells remained filamentous ( Figure 2D). However, EGF treatment resulted in the translocation of b-catenin from the cytoplasm and cell junctions to discrete regions of the nucleus in certain population of cells ( Figure 2E), consistent with the activation of the b-catenin-mediated pathways in response to EGF-associated EMT events (Polette et al, 2007).…”
Section: Jak2/stat3 Status In Ovarian Carcinomassupporting
confidence: 75%
“…In contrast, the localisation of vimentin in both control and EGF-treated cells remained filamentous ( Figure 2D). However, EGF treatment resulted in the translocation of b-catenin from the cytoplasm and cell junctions to discrete regions of the nucleus in certain population of cells ( Figure 2E), consistent with the activation of the b-catenin-mediated pathways in response to EGF-associated EMT events (Polette et al, 2007).…”
Section: Jak2/stat3 Status In Ovarian Carcinomassupporting
confidence: 75%
“…To further examine whether Dicer is required in cell-cell adhesion, expression and distribution of the tight junction protein ZO-1 (zona occludens-1, encoded by the Tjp1 gene) was analyzed on cultured epicardial cells. Translocation of ZO-1 between the cell surface and cytoplasm has been implicated in EMT (33). In control epicardial explants, ZO-1 expression was weak and diffuse, and its distribution was not restricted to the cell surface, a hallmark of cells undergoing EMT (Fig.…”
Section: Epicardial Deletion Of Dicer Leads To Perinatalmentioning
confidence: 96%
“…The Wnt/β-catenin pathway is fundamental in the epithelial-mesenchymal transition (EMT), an important step in oncogenic transformation, which includes cell invasion and metastasis (36)(37)(38). The nuclear translocation of β-catenin leads to the downregulation of E-cadherin and subsequent induction of EMT (39), whereas the upregulation of β-catenin is associated with the invasion and metastasis of several types of solid tumor (40)(41)(42). A previous study found that TRIM24 knockdown decreased the levels of EMT-associated factors in hepatocellular carcinoma.…”
Section: A B C D E Fmentioning
confidence: 99%